2014
DOI: 10.1007/s10912-014-9322-4
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Narratives of Health: (Re)Placing Folk-Medicine within Irish Health Histories

Abstract: With the increased acceptance of complementary and alternative medicine (CAM) within society, new research reflects deeper folk health histories beyond formal medical spaces. The contested relationships between formal and informal medicine have deep provenance and as scientific medicine began to professionalise in the 19th century, lay health knowledges were simultaneously absorbed and disempowered (Porter 1997). In particular, the 'medical gaze' and the responses of informal medicine to this gaze were framed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Although traditional medicines are quite well known for Chinese and African traditions, many European traditions have almost disappeared or are the preserve of rural backwaters. Some of the last vestiges of these traditions can be found on the furthest fringes of Western Europe on the island of Ireland [15]. Although some of this traditional medicine has been partially documented [16,17], many of the traditional cures were closely guarded secrets passed down through generations that have now almost faded from memory.…”
Section: Introductionmentioning
confidence: 99%
“…Although traditional medicines are quite well known for Chinese and African traditions, many European traditions have almost disappeared or are the preserve of rural backwaters. Some of the last vestiges of these traditions can be found on the furthest fringes of Western Europe on the island of Ireland [15]. Although some of this traditional medicine has been partially documented [16,17], many of the traditional cures were closely guarded secrets passed down through generations that have now almost faded from memory.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in North America, the narrative approach in research on suicide among indigenous peoples was found compatible with indigenous culture and facilitated research (40). On the other hand, in Ireland, indigenous health narratives support fluid relationships with biomedicine and elicit broader cultural debates and belief models (41). Hence, in this work, qualitative research with a narrative approach is consolidated as a research methodology appropriate toward determining the constructions encompassed by the concept of the human life process and circulated among Rev.…”
Section: Discussionmentioning
confidence: 99%
“…Este tipo de medicina merece una especial consideración como fenómeno que se mantiene en las diferentes latitudes donde aún existen comunidades de origen primitivo que conservan principios de la historia de la medicina en sus diferentes manifestaciones con concepciones particulares sobre salud y enfermedad, con resultados positivos dentro de sus comunidades. (102)(103)(104)(105) Como se puede obervar, el concepto de Medicina Alternativa no se refiere simplemente a la utilización de cualquier estrategia que no esté contemplada dentro de la medicina convencional o tradicional, sino que realmente corresponde al ejercicio adecuado de otros sistemas de practicar la medicina que tienen una fundamentación histórica y social y para lo cual se requiere el conocimiento adecuado de cada disciplina.…”
Section: Medicina Tradicional Indígenaunclassified